Pemetaan Penelitian Bisnis Pariwisata Halal: Analisis Bibliometrik Pada Database Scopus - Purwantoro, Arif; Haryanto, Tri; Nurhidayati, Sri Endah (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
The largest market share in the post-pandemic era is controlled by Middle Eastern countries, as evidenced by the fact that the football industry currently owns clubs from there. On the other hand, there are also increasing requests from Muslim tourists who want to carry out their lifestyle by religious teachings. The tourism industry must respond by facilitating halal tourism because most Middle Eastern tourists are Muslim. This study aims to map and briefly describe the bibliometrics of the halal tourism business that can be used to examine trends, patterns, and developments. This study used article publication data from the Scopus database from 1997-2023 with the theme "halal tourism business" and obtained 60 articles using the VOSviewer application. The results showed that articles with the theme of the halal tourism business in the Scopus database were first published in 1997. The most published articles with the theme of the halal tourism business were in 2022 (12 documents), while the journal that published the most was "Journal of Islamic Marketing". The most affiliated journals are from the University of Malaysia Kelantan, the most published journals are from Indonesia, and the most subjects are business, management, and accounting. Keywords related to the halal tourism business include Islamic religion, Muslim traveler, halal tourism, halal tourism products, halal business, and halal tourism industry.